SIKAP DIGITAL NATIVES TERHADAP INFORMASI HOAX DI FACEBOOK MENJELANG PILPRES 2019 - Jaduk Gilang Pembayun; RM Mahendradi (Universitas Tidar, 2019)
Abstract: The need for information is increasing, making the media develop into various formsand functions, which make it easier for humans to meet their needs. The presence of the internethas brought revolution and innovation in the way humans communicate and obtain information.The internet has succeeded in overcoming classic human problems, because the limitations ofdistance, space and time are no longer a significant obstacle. Social networks have a positiveimpact on community communication. But behind it all there are also negative impacts that arefelt by many users of social media. The negative impact is caused because the community is notgood at choosing and sorting out the good ones and the bad ones. This study aims to find outthe attitude of Digital Natives about how the news is especially related to politics on Facebookahead of the 2019 Presidential Election. This study uses qualitative methods that seek to digdeep information, and be open to all responses and answers. The conclusion of this research isthat all informants agreed to keep checking a news / information that they found on Facebookto be more convincing and know the truth of the news they saw. Given the current many newshoaxes that make people dibelief in the news / information on social media.